Immune development differs between preterm newborns fed mothers’ own milk and donor milk - Ziyang Tan; Wen Zhong; Hanna Danielsson; Aron Arzoomand; Tadepally Lakshmikanth; Qi Chen; Jaromir Mikes; Jun Wang; Yang Chen; Anna James; Anders K. Nilsson; Anders Elfvin; et al. (iScience)
Summary: Extremely preterm infants are at risk of immune-mediated complications such as infections and inflammatory conditions like bronchopulmonary dysplasia and necrotizing enterocolitis. Preterm infants are immunologically distinct from term infants at birth, but subsequently undergo adaptive postnatal changes resulting in immunological convergence during their first 3 months. Here, we performed a systems-level analysis of immune development in 72 preterm infants born as early as 22 weeks to investigate factors associated with variation. We find similar immune trajectories during early postnatal immune development but occurring more slowly in infants born at 22–24 weeks. Immune development showed a greater resemblance to that of term-born children in preterm infants fed mother’s own milk compared to donor milk. This developmental normalization was manifested by NK cell development and was not explained by differences in microbial colonization between feeding groups, possibly suggesting direct effects of bioactive milk molecules on developing immune cells in extremely preterm infants.